A prospective randomized comparison of vaginal hysterectomy, laparoscopically assisted vaginal hysterectomy, and total laparoscopic hysterectomy in women with benign uterine disease - Drahonovsky, Jan; Haakova, Lucia; Otcenasek, Michal; Krofta, Ladislav; Kucera, Eduard; Feyereisl, Jaroslav (European journal of obstetrics, gynecology, and reproductive biology, 2010)
OBJECTIVES: To compare the clinical results of three minimally invasive hysterectomy techniques: vaginal hysterectomy (VH), laparoscopically assisted vaginal hysterectomy (LAVH), and total laparoscopic hysterectomy (TLH). STUDY DESIGN: A prospective, randomized study was performed at a tertiary care center between March 2004 and October 2005. A total of 125 women indicated to undergo hysterectomy for benign uterine disease were randomly assigned to three different groups (40 VH, 44 LAVH, and 41 TLH). Outcome measures, including operating time, blood loss, rate of complications, inflammatory response, febrile morbidity, consumption of analgesics, and length of hospital stay, were assessed and compared between groups. RESULTS: Vaginal hysterectomy had the shortest operating time (66 min) and smallest drop in hemoglobin. However, there were technical problems with salpingo-oophorectomy from the vaginal approach (3/20 cases) and this group had a significantly higher rate of febrile complications (20%) compared to LAVH (2.3%) and TLH (7.3%). The increase in inflammatory markers was higher in vaginal hysterectomy patients. Laparoscopically assisted vaginal hysterectomy had an acceptable operating time (85 min), a low complication rate, lack of severe post-operative complications, and the lowest consumption of analgesics. However, it had the highest blood loss. Total laparoscopic hysterectomy had the longest operating time (111 min) and severe complications occurred only in this group. Conversions to another hysterectomy method occurred in all three groups, most of these conversions were to LAVH. CONCLUSIONS: Based on our results, in women with non-malignant disease of the uterus, LAVH and VH seem to be the preferred hysterectomy techniques for general gynecological surgeons. Vaginal hysterectomy had the shortest operating time and least drop in hemoglobin, making it a suitable method for women for whom the shortest duration of surgery and anesthesia is optimal. LAVH is a versatile procedure, combining the advantages of both the vaginal and laparoscopic approach, and is preferable in cases when oophorectomy is required. Total laparoscopic hysterectomy did not appear to offer any significant benefits over the other two methods and should be strictly indicated in women where neither VH nor LAVH are feasible and should only be performed by very experienced laparoscopists.
Keywords: Hysterectomy, Vaginal; Uterine Diseases; nemoci dělohy; laparoskopie; lidé středního věku; hysterektomie vaginální; lidé; Female; prospektivní studie; Laparoscopy; Prospective Studies; Middle Aged; ženské pohlaví; Humans